What's on your hard drive?. - O'Hanlon, Charlene (ACM queue : architecting tomorrow's computing., 2005)
As 2005 comes to a close, we'd like to thank all the readers who've submitted to WOYHD. We've seen a lot of tools mentioned over the past year--some popular, and some we'd never heard of. With 2006 on the horizon, we'd like a lot more of the same. So send us your rants, raves, and more new tools that you absolutely can't live without--or can't bear to use. And lest we forget, if your submission is chosen, you'll receive one of our stylish Queue coffee mugs--destined to become a modern classic. So please keep 'em coming at www.acmqueue.com.